Penggunaan Metode Struktural Analitik Sintetik dalam Meningkatkan Kemampuan Membaca Permulaan pada Pembelajaran Pendidikan Agama Katolik di Sekolah Dasar - Elisa Bomba; Yanto Sandy Tjang; Felisitas Yuswanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to evaluate the effectiveness of the Structural Analytic Synthetic (SAS) method in enhancing the early reading skills of first-grade students in Catholic Religious Education at SD YPPK Yohanes Paulus II Obaa, Mappi Regency, South Papua Province. The study employed a Classroom Action Research approach using a cyclical model comprising the stages of planning, implementation, observation, and reflection, conducted over two cycles. The research subjects consisted of 25 students, and data were collected through reading tests, classroom observations, and documentation. The results indicated a significant improvement in students’ early reading skills, with learning mastery increasing from 61% in the first cycle to 100% in the second cycle. This success was associated with the implementation of the SAS method through structured learning stages, progressing from sentences to words, syllables, and letters, accompanied by the use of varied media and intensive teacher guidance. In addition to improving reading skills, the SAS method was also found to enhance students’ interest, participation, and learning motivation. Therefore, the SAS method is recommended as an effective strategy for teaching early reading to young elementary school students, particularly within the context of Catholic Religious Education.